Opinions of contemporary Muslim Jurists on the registration of marriages - Mahmud , Mek Wok (IIUM Press, 2011)
Registration of marriages is one of the debatable issues among contemporary Muslim scholars. Considering the fact that it was not implemented during the Prophet S s. a. w time, many scholars discuss the validity ofits practice as one ofShari 'ah requirements to recognize a marriage contract. Thus, the main objective of this paper is to critically analyze the opinions of Muslim contemporary scholars on the registration of marriage as a requirement for a marriage contract to be recognized and officially authenticated, as currently practiced in many Muslim countries. This paper will give adequate attention to the issue regarding the Shari'ah status, as the registration of marriage has no basis among the Shari'ah requirements for a valid marriage contract. At the end of this research, findings based on the general principles of Shari'ah show that the registration of marriage, though not basically required for a Shari'ah compliant marriage, cannot as such be regarded as alien to Islamic law, as it is comfortably fitted into those aspects of Shari'ah meant for accommodation of contemporary issues. Prominent among these are al-Qiyas, Saddal-Dhara'i'. al-Istilsan, Maqasid al-shari'ah and as-Siyasah al-shar'iyyah otherwise known in "the principles of Islamic Jurisprudence" as secondary sources of Shari'ah.